Comparison of Optimum Balance Values For Different Coefficients of Spherical Aberration of Optical System Including Different Apertures - Hassan, Al. Badr; Ali, H. Mumtaz; Rabee, R. Faisal (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The optimum balance values for different coefficient of spherical aberration (third and fifth degree also focal shift) were studied, the optical system includes different apertures (circle, ellipse, square and triangle) using point spread function (PSF).       By using (Marechal) method; the minimum value of mean square of variance in wave front was founded, so we can get the maximum of central intensity according to (Strehl) criterion.